REGENERASI BEBERAPA EKSPLAN TANAMAN JAMBU BIJI (Psidium guajava L.) PADA MEDIA KOMBINASI BAP DAN IBA SECARA IN VTRO - Rani Pratiwi; Susiyanti .; Zahratul Millah; Karyanti . (Jurnal Agroekoteknologi, 2011)
The experimen was done to know the best combination of the treatment with the used of different types of explan conducted in Tissue Culture Laboratory, 633 Biotechnology Building - Center for the Assessment and Application of Biotechnology (Biotech Center of BPPT), Agency For The Assesment and Application of Technology (PUSPIPTEK), Serpong July to October 2009. The results of this study is expected to be used as a reference in the process of guava rapid regeneration (in vitro) in order to support quality improvement activities of the guava plant. Research used Completely Randomized Designed (RAL) with 3 factors, BAP concentrations level (0; 2.5; 5; 7.5 and 10 mg/L), IBA concentrations level (0 and 0.5 mg/L) and types of explan (cotyledon, hipokotil and tip). Results showed that combination treatment of 0 mg/L BAP and 0.5 mg/L IBA was good for callus initiation hipokotil and cotyledon at 2 weeks after palnting, diameter of callus in the cotyledon and the number of roots. Treatments combination which most effective in inducing shoot growth is the tip treatment with the concentration of 10 mg/L BAP and 0.5 mg/L IBA in 6 weeks after planting. Concentration of 2.5 mg/L BAP and 0.5 mg/L IBA is a combination of the best growth regulator substances to the shoot height, number of leaves and node. Provision of BAP, IBA and Explan either single or interaction between the second and third generally provide a significant effect on the growth of Psidium guajava L.Key words: guava plant, Psidium guajava L., BAP, IBA